Flexible polyvinyl chloride electrical adhesive tape and processing method thereof
Through reasonable formulation and processing steps, low-cost, environmentally friendly soft polyvinyl chloride electrical tape is used to make raw materials such as polyvinyl chloride, which solves the problems of environmental pollution and high production costs in the existing technology, and achieves good performance and economicality of the tape sex.
Patent Information
- Application Number
- CN202411580613.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-01-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing soft polyvinyl chloride electrical tape production process has problems such as serious environmental pollution, high production costs and waste of resources, especially because the organic solvents used and high-cost high-temperature resistant polyvinyl chloride films make it difficult to meet market demand.
Use polyvinyl chloride, polylactic acid, poly terephthalic acid-butylene adipate, benzoate plasticizer, nano-treated rubber, calcium and zinc stabilizer, nano-grade fly ash, natural animal and vegetable oils and mineral oils The raw materials such as ethanol and water are used as solvents to carry out reasonable formulation and processing steps to form low-cost and environmentally friendly tape products.
It has achieved low production costs, environmentally friendly and resource-friendly tape products, with good biodegradability, mechanical strength, adhesive properties and oxidation resistance, extending the service life of tape and reducing environmental pollution.
Smart Images

Figure CN119264834A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of light industry, in particular to a soft polyvinyl chloride electrical tape and a processing method thereof. Background Art
[0002] Soft polyvinyl chloride (SPVC) electrical tape is a tape product widely used in electrical insulation and bundling. In the existing production process, the base film is coated on the soft polyvinyl chloride film substrate with a solvent-based rubber pressure-sensitive adhesive, and then dried, rolled and slit. However, this process has many disadvantages, including serious environmental pollution, high production costs and safety hazards.
[0003] In the production process, the use of organic solvents such as toluene not only causes a waste of resources, but also causes serious environmental pollution. A very small amount of organic solvents remain in the adhesive layer of the adhesive tape product, which will be slowly released during use, further polluting the use environment. In addition, the high-temperature resistant polyvinyl chloride film and UV-curable hot-melt pressure-sensitive adhesive used in the existing high-temperature resistant polyvinyl chloride tape production method are extremely expensive and difficult to be accepted by the mass consumer market. Summary of the invention
[0004] 1. Technical issues to be resolved
[0005] In view of the deficiencies in the prior art, the present invention provides a soft polyvinyl chloride electrical tape and a processing method thereof, which has the advantages of low production cost, environmental protection and full utilization of resources, and solves the problems of high production cost, environmental pollution and waste of resources in the production process.
[0006] (II) Technical solution
[0007] To achieve the above-mentioned purpose, the present invention provides the following technical scheme: a soft polyvinyl chloride electrical tape, wherein the tape raw material consists of a base film raw material part and a glue layer raw material part, and the tape raw materials and their weight parts are: 45-52 parts of polyvinyl chloride; 15-20 parts of polylactic acid; 1-4 parts of polybutylene terephthalate-adipate; 45-60 parts of benzoate plasticizer; 14-18 parts of nano-treated rubber; 1.2-1.5 parts of calcium zinc stabilizer; 5-8 parts of color paste; 5-20 parts of nano-grade fly ash; 4-7 parts of trioctyl trimellitate; 8-14 parts of thermoplastic polyurethane; 8-17 parts of tin-doped porous silica; 14-20 parts of natural animal and vegetable oils and mineral oils; 6-10 parts of molybdenum oxide; 9-14 parts of tripropane ester; 22-30 parts of ethanol; and 35-40 parts of water.
[0008] Preferably, the nano-treatment process of the nano-treated rubber is: mixing natural rubber and nano-silicon dioxide in a weight ratio of 1:4, and cutting and uniformly dispersing the mixture using a high-speed shearing stirrer to form a nano-treated rubber raw material.
[0009] Preferably, the preparation process of the nano-scale fly ash is as follows: fly ash with a silicon dioxide content of 20% is selected as the basic material, and the fly ash is put into a jet mill for pulverization to make its particle size reach a raw material with an average diameter of 60-80nm.
[0010] Preferably, the weight ratio of the natural animal and plant oils to the mineral oil is 6:1.
[0011] Preferably, a method for processing a soft polyvinyl chloride electrical tape is processed according to the raw materials and weight portions of the soft polyvinyl chloride electrical tape described above, and comprises the following processing steps:
[0012] Step 1: Raw material preparation: prepare all raw materials in the raw material formula by weight;
[0013] Step 2, solvent selection: select ethanol and water as solvent;
[0014] Step 3, base film preparation: polyvinyl chloride, polylactic acid and polybutylene terephthalate-adipate are added into a mixing kettle A, ethanol and water are added, and after setting conditions, mixing, heating and stirring are performed, and the base film is formed by extruding through an extruder;
[0015] Step 4, adhesive layer part: add benzoate plasticizer, nano-treated rubber, calcium zinc stabilizer, color paste, nano-scale fly ash, trioctyl trimellitate, thermoplastic polyurethane, tin-doped porous silica, natural animal and vegetable oils and mineral oils, molybdenum oxide and tripropane ester into another mixing kettle B, add the remaining ethanol and water, set the conditions, mix, heat and stir to form an adhesive layer solution;
[0016] Step 5: coating: coating the prepared adhesive layer solution on the base film;
[0017] Step 6: Curing: The coated base film is placed in an oven for drying, and the finished electrical tape is produced;
[0018] Step 7. Quality inspection: Test the appearance, thickness, width, bonding strength and electrical performance of the finished electrical tape.
[0019] Preferably, the setting conditions of step three are: setting the temperature of mixing kettle A to 78-85°C, setting the stirring speed of mixing kettle A to 100r / min, setting the temperature of extruder to 60-80°C, and setting the calendering speed of extruder to 2.5-3.5m / min.
[0020] Preferably, the setting conditions of step 4 are: setting the temperature of mixing kettle B to 60-65° C., and setting the stirring speed of mixing kettle B to 200 r / min.
[0021] Preferably, the weight ratio of ethanol to water in step three is 6:2, and the weight ratio of ethanol to water in step four is 5:4.
[0022] Preferably, in step five, the prepared adhesive layer solution is coated on the base film using a coating machine, and the coating thickness is controlled between 0.12 mm and 0.14 mm.
[0023] Preferably, the curing temperature in step six is 100-105° C., and after curing, the mixture is cooled to room temperature under natural conditions.
[0024] Compared with the prior art, the present invention provides a soft polyvinyl chloride electrical tape and a processing method thereof, which has the following beneficial effects:
[0025] 1. The present invention adopts a reasonably matched raw material formula. The addition of polylactic acid and polybutylene terephthalate-adipate in the formula makes the tape have good biodegradability, thereby reducing environmental pollution. The combination of these two materials not only enhances the elasticity and tear resistance of the tape, but also improves the overall mechanical strength of the tape. At the same time, the synergistic effect of nano-treated rubber and nano-level fly ash can improve the bonding performance of the tape. The addition of fly ash not only enhances the strength and hardness of the tape, but its waste utilization feature also helps to reduce production costs. The combined use of natural animal and plant oils and mineral oils increases the lubricity and oxidation resistance of the tape, thereby reducing the friction coefficient of the tape during use, reducing the wear of the tape, and extending the life of the tape. The new combination of the above raw materials enables the finished tape to maintain stable performance while achieving environmental protection and economic purposes. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a processing flow chart of the present invention. DETAILED DESCRIPTION
[0027] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] See also Figure 1 , a soft polyvinyl chloride electrical tape, the tape raw material consists of a base film raw material part and an adhesive layer raw material part;
[0029] The weight parts of adhesive tape raw materials and their functions are:
[0030] 45-52 parts of polyvinyl chloride;
[0031] Polyvinyl chloride: As the main raw material of the base film, it provides the basic physical and chemical properties of the tape, such as insulation and mechanical strength;
[0032] Polylactic acid (PLA) 15-20 parts;
[0033] Polylactic acid: As a biodegradable plastic, it has good mechanical properties and low production costs, which increases the environmental performance and biodegradability of the tape;
[0034] 1-4 parts of polybutylene terephthalate adipate (PBAT);
[0035] Polybutylene terephthalate-adipate: As a biodegradable resin, PBAT provides good processing performance and biodegradability, and its degradation products are carbon dioxide and water, which are pollution-free;
[0036] 45-60 parts of benzoate plasticizer;
[0037] Benzoate plasticizers: increase the flexibility and processability of PVC, making it easier to shape and process;
[0038] 14-18 parts of nano-treated rubber;
[0039] Nano-treated rubber: improves the flexibility and elasticity of the tape and increases the adhesion between the adhesive layer and the base film;
[0040] Calcium zinc stabilizer 1.2-1.5 parts;
[0041] Calcium zinc stabilizer: provides thermal stability to prevent thermal degradation of PVC during processing, and also acts as an environmentally friendly stabilizer to reduce the use of heavy metals;
[0042] Color paste 5-8 parts;
[0043] Color paste: Gives the tape a specific color to identify and distinguish tapes for different purposes;
[0044] 5-20 parts of nano-level fly ash;
[0045] Nano-scale fly ash: enhances the mechanical properties and heat resistance of the tape and acts as a low-cost filler;
[0046] 4-7 parts of trioctyl trimellitate;
[0047] Trioctyl trimellitate: As a plasticizer, it increases the flexibility and cold resistance of the tape;
[0048] Thermoplastic polyurethane 8-14 parts;
[0049] Thermoplastic polyurethane: improves the wear resistance and oil resistance of the tape and increases its service life in harsh environments;
[0050] 8-17 parts of tin-doped porous silica;
[0051] Tin-doped porous silica: as a filler, it improves the thermal stability and mechanical properties of the tape while increasing its chemical resistance;
[0052] 14-20 parts of natural animal and vegetable oils and mineral oils;
[0053] Natural animal and vegetable oils and mineral oils: act as plasticizers and softeners to improve the flexibility and processability of the tape;
[0054] 6-10 parts of molybdenum oxide;
[0055] Molybdenum oxide: acts as a lubricant and anti-wear agent to reduce friction and wear of the tape during winding and use;
[0056] 9-14 parts of tripropane ester;
[0057] Tripropane ester: as a plasticizer, it increases the flexibility and cold resistance of the tape;
[0058] 22-30 parts of ethanol;
[0059] 35-40 parts water;
[0060] Ethanol and water: used as solvents to dissolve and mix various raw materials, and to help form a uniform glue layer during the coating process.
[0061] Specifically, the nano-treatment process of the nano-treated rubber is as follows: natural rubber and nano-silicon dioxide are mixed in a weight ratio of 1:4, and the mixture is cut and evenly dispersed using a high-speed shearing mixer to form a nano-treated rubber raw material for later use.
[0062] Specifically, the preparation process of nano-scale fly ash is as follows: fly ash with a silicon dioxide content of 20% is selected as the basic material, and the fly ash is put into a jet mill for pulverization to make the particle size reach a raw material with an average diameter of 60-80nm.
[0063] Specifically, the weight ratio of natural animal and vegetable oil to mineral oil is 6:1.
[0064] Specifically, a method for processing a soft polyvinyl chloride electrical tape is processed according to the raw materials and weight portions of the soft polyvinyl chloride electrical tape mentioned above, and includes the following processing steps:
[0065] Step 1: Raw material preparation: prepare all raw materials in the raw material formula by weight;
[0066] Step 2, solvent selection: select ethanol and water as solvent;
[0067] Step 3, base film preparation: polyvinyl chloride, polylactic acid and polybutylene terephthalate-adipate are added into a mixing kettle A, ethanol and water are added, and after setting conditions, mixing, heating and stirring are performed, and the base film is formed by extruding through an extruder;
[0068] Step 4, adhesive layer part: add benzoate plasticizer, nano-treated rubber, calcium zinc stabilizer, color paste, nano-scale fly ash, trioctyl trimellitate, thermoplastic polyurethane, tin-doped porous silica, natural animal and vegetable oils and mineral oils, molybdenum oxide and tripropane ester into another mixing kettle B, add the remaining ethanol and water, set the conditions, mix, heat and stir to form an adhesive layer solution;
[0069] Step 5: coating: coating the prepared adhesive layer solution on the base film;
[0070] Step 6: Curing: The coated base film is placed in an oven for drying, and the finished electrical tape is produced;
[0071] Step 7. Quality inspection: Test the appearance, thickness, width, bonding strength and electrical performance of the finished electrical tape.
[0072] Specifically, the setting conditions of step three are: setting the temperature of mixing kettle A to 78-85°C, setting the stirring speed of mixing kettle A to 100 r / min, setting the temperature of extruder to 60-80°C, and setting the calendering speed of extruder to 2.5-3.5 m / min.
[0073] Specifically, the setting conditions of step 4 are: setting the temperature of mixing kettle B to 60-65° C., and setting the stirring speed of mixing kettle B to 200 r / min.
[0074] Specifically, the weight ratio of ethanol to water in step three is 6:2, and the weight ratio of ethanol to water in step four is 5:4.
[0075] Specifically, in step five, a coating machine is used to coat the prepared adhesive layer solution on the base film, ensuring that the coating thickness is controlled between 0.12 mm and 0.14 mm to meet the performance requirements of the soft polyvinyl chloride electrical tape.
[0076] Specifically, in step six, the curing temperature is 100-105° C., and after curing, the mixture is cooled to room temperature under natural conditions.
[0077] Example 1
[0078] The invention discloses a soft polyvinyl chloride electrical tape, wherein the raw materials of the tape consist of a base film raw material part and an adhesive layer raw material part, and the raw materials of the tape and their weight parts are as follows: 45 parts of polyvinyl chloride; 18 parts of polylactic acid; 3 parts of polybutylene terephthalate-adipate; 50 parts of benzoate plasticizer; 16 parts of nano-treated rubber; 1.22 parts of calcium zinc stabilizer; 6 parts of color paste; 14 parts of nano-grade fly ash; 5 parts of trioctyl trimellitate; 9 parts of thermoplastic polyurethane; 8 parts of tin-doped porous silica; 15 parts of natural animal and vegetable oil and mineral oil; 6 parts of molybdenum oxide; 9 parts of tripropane ester; 22 parts of ethanol; and 38 parts of water.
[0079] Example 2
[0080] A soft polyvinyl chloride electrical tape, the tape raw materials consist of a base film raw material part and an adhesive layer raw material part, and the tape raw materials and their weight parts are: 52 parts of polyvinyl chloride; 20 parts of polylactic acid; 4 parts of polybutylene terephthalate-adipate; 59 parts of benzoate plasticizer; 11 parts of nano-treated rubber; 1.2 parts of calcium zinc stabilizer; 6 parts of color paste; 6 parts of nano-level fly ash; 6 parts of trioctyl trimellitate; 8 parts of thermoplastic polyurethane; 14 parts of tin-doped porous silica; 15 parts of natural animal and vegetable oils and mineral oils; 9 parts of molybdenum oxide; 14 parts of tripropane ester; 25 parts of ethanol; and 36 parts of water.
[0081] Example 3
[0082] The invention discloses a soft polyvinyl chloride electrical tape, wherein the raw materials of the tape consist of a base film raw material part and an adhesive layer raw material part, and the raw materials of the tape and their weight parts are as follows: 47 parts of polyvinyl chloride; 15 parts of polylactic acid; 1 part of polybutylene terephthalate-adipate; 45 parts of benzoate plasticizer; 14 parts of nano-treated rubber; 1.2 parts of calcium zinc stabilizer; 8 parts of color paste; 18 parts of nano-grade fly ash; 7 parts of trioctyl trimellitate; 9 parts of thermoplastic polyurethane; 13 parts of tin-doped porous silica; 18 parts of natural animal and vegetable oils and mineral oils; 8 parts of molybdenum oxide; 14 parts of tripropane ester; 24 parts of ethanol; and 36 parts of water.
[0083] Example 3
[0084] The invention discloses a soft polyvinyl chloride electrical tape, wherein the raw materials of the tape consist of a base film raw material part and an adhesive layer raw material part, and the raw materials of the tape and their weight parts are as follows: 47 parts of polyvinyl chloride; 15 parts of polylactic acid; 1 part of polybutylene terephthalate-adipate; 45 parts of benzoate plasticizer; 14 parts of nano-treated rubber; 1.2 parts of calcium zinc stabilizer; 8 parts of color paste; 18 parts of nano-grade fly ash; 7 parts of trioctyl trimellitate; 9 parts of thermoplastic polyurethane; 13 parts of tin-doped porous silica; 18 parts of natural animal and vegetable oils and mineral oils; 8 parts of molybdenum oxide; 14 parts of tripropane ester; 24 parts of ethanol; and 36 parts of water.
[0085] Comparative Example 1
[0086] A soft polyvinyl chloride electrical tape, the tape raw materials consist of a base film raw material part and an adhesive layer raw material part, the tape raw materials and their weight parts are: 60 parts of polyvinyl chloride; 3 parts of polybutylene terephthalate-adipate; 50 parts of benzoate plasticizer; 16 parts of nano-treated rubber; 1.22 parts of calcium zinc stabilizer; 6 parts of color paste; 14 parts of nano-level fly ash; 5 parts of trioctyl trimellitate; 9 parts of thermoplastic polyurethane; 8 parts of tin-doped porous silica; 15 parts of natural animal and plant oils and mineral oils; 6 parts of molybdenum oxide; 9 parts of tripropane ester; 22 parts of ethanol; 38 parts of water (remove 18 parts of polylactic acid in Example 1, and increase the polyvinyl chloride to 60 parts).
[0087] Comparative Example 2
[0088] A soft polyvinyl chloride electrical tape, the tape raw materials consist of a base film raw material part and an adhesive layer raw material part, the tape raw materials and their weight parts are: 52 parts of polyvinyl chloride; 24 parts of polylactic acid; 59 parts of benzoate plasticizer; 11 parts of nano-treated rubber; 1.2 parts of calcium zinc stabilizer; 6 parts of color paste; 6 parts of nano-level fly ash; 6 parts of trioctyl trimellitate; 8 parts of thermoplastic polyurethane; 14 parts of tin-doped porous silica; 15 parts of natural animal and plant oils and mineral oils; 9 parts of molybdenum oxide; 14 parts of tripropane ester; 25 parts of ethanol; 36 parts of water (4 parts of polybutylene terephthalate-adipate in Example 2 are removed and polylactic acid is increased to 24 parts).
[0089] Comparative Example 3
[0090] A soft polyvinyl chloride electrical tape, the tape raw materials consist of a base film raw material part and an adhesive layer raw material part, the tape raw materials and their weight parts are: 47 parts of polyvinyl chloride; 15 parts of polylactic acid; 1 part of polybutylene terephthalate-adipate; 45 parts of benzoate plasticizer; 14 parts of nano-treated rubber; 1.2 parts of calcium zinc stabilizer; 8 parts of color paste; 18 parts of nano-grade fly ash; 7 parts of trioctyl trimellitate; 9 parts of thermoplastic polyurethane; 13 parts of tin-doped porous silica; 18 parts of natural animal and vegetable oils and mineral oils; 8 parts of molybdenum oxide; 14 parts of tripropane ester; 24 parts of ethanol; 36 parts of water (the nano-treated rubber in Example 3 is replaced by ordinary rubber, and the nano-grade fly ash is replaced by ordinary fly ash, and the weight parts remain unchanged).
[0091] Comparative Example 4
[0092] A soft polyvinyl chloride electrical tape, the tape raw materials consist of a base film raw material part and an adhesive layer raw material part, the tape raw materials and their weight parts are: 47 parts of polyvinyl chloride; 15 parts of polylactic acid; 1 part of polybutylene terephthalate-adipate; 45 parts of benzoate plasticizer; 14 parts of nano-treated rubber; 1.2 parts of calcium zinc stabilizer; 8 parts of color paste; 18 parts of nano-grade fly ash; 7 parts of trioctyl trimellitate; 9 parts of thermoplastic polyurethane; 13 parts of tin-doped porous silica; 18 parts of natural animal and vegetable oils and mineral oils; 8 parts of molybdenum oxide; 14 parts of tripropane ester; 24 parts of ethanol; 36 parts of water (the natural animal and vegetable oils and mineral oils in Example 3 are replaced by paraffin-based plasticizers, and their weight parts remain unchanged).
[0093] The raw material formulas of Examples 1-3 and Comparative Examples 1-4 were processed into finished tapes using the processing method of the present invention, and the appearance, thickness, width, bonding strength and electrical performance of the finished tapes were tested. The test data are shown in Table 1 below:
[0094] Table 1
[0095]
[0096]
[0097] From Table 1, we can get the following analysis results:
[0098] Appearance: The appearance test results of all samples prepared in the embodiments and comparative examples were "qualified", indicating that the electrical tapes of all embodiments and comparative examples met the standard requirements in appearance without obvious differences.
[0099] Thickness: The thickness of the tapes made in Example 1, Example 2 and Example 3 are 0.13 mm, 0.14 mm and 0.12 mm, respectively, all within the range of 0.12 mm to 0.14 mm, meeting the prescribed thickness requirement, while the thickness of the tape in Comparative Example 1 is 0.15 mm, exceeding the prescribed range, and the thickness of the tapes in Comparative Example 2, Comparative Example 3 and Comparative Example 4 are 0.14 mm, 0.13 mm and 0.14 mm, respectively, all within the prescribed range.
[0100] Width: The width of all samples is 50mm, which meets the specified width requirements and there is no difference.
[0101] Bonding strength: The bonding strengths of Example 1, Example 2 and Example 3 are 2.5 N / 25 mm, 2.6 N / 25 mm and 2.4 N / 25 mm, respectively, which are all higher than the bonding strength of the comparative example, while the bonding strengths of comparative examples 1 to 4 gradually decrease, which are 2.3 N / 25 mm, 2.2 N / 25 mm, 2.1 N / 25 mm and 2.0 N / 25 mm, respectively.
[0102] Electrical performance: The electrical performance of Examples 1, 2 and 3 is all 10 kV / mm, which is the best performance, while the electrical performance of Comparative Example 1 is 9 kV / mm, slightly lower than that of the embodiment. The electrical performance of Comparative Example 2 is also 9 kV / mm, the same as Comparative Example 1. The electrical performance of Comparative Example 3 is 8 kV / mm, which is further reduced. The electrical performance of Comparative Example 4 is the lowest, which is 7 kV / mm.
[0103] Finally got the information:
[0104] The adhesive tapes of Examples 1 to 3 are superior to those of Comparative Examples 1 to 4 in terms of bonding strength and electrical properties, indicating that the examples are within the raw material formula range of the present invention and can improve the performance of the adhesive tape in combination with their processing methods. The thickness of Comparative Example 1 exceeds this range, indicating that removing 18 parts of polylactic acid and increasing polyvinyl chloride to 60 parts in Example 1 has an impact on the thickness of the finished product. The electrical properties of Comparative Example 4 are the lowest, indicating that the use of paraffin-based plasticizers instead of natural animal and vegetable oils and mineral oils will affect the electrical properties of the adhesive tape.
[0105] The raw material formulas of Examples 1-3 and Comparative Examples 1-4 were used to make finished tapes using the processing method of the present invention, and the prices of the raw materials were compared. The data obtained are shown in Table 2 below:
[0106] Table 2
[0107]
[0108] The following information is obtained from Table 2:
[0109] The proportion of raw material cost in the embodiment is compared with that in the comparative example, and changes are made in the use of polylactic acid, PBAT, nano-fly ash, animal and vegetable oils and mineral oils. The changes in the above ingredients will affect the performance and cost of the tape. The increase in the use of polylactic acid in comparative example 2 will increase the cost, while no animal and vegetable oils and mineral oils are used in comparative example 4, and a more expensive paraffin-based plasticizer is used.
[0110] Therefore, it is concluded that: in the embodiment, through the reasonable combination of raw material formula, the addition of polylactic acid and polybutylene terephthalate-adipate in the formula makes the tape have good biodegradability, thereby reducing environmental pollution. The combination of these two materials not only enhances the elasticity and tear resistance of the tape, but also improves the overall mechanical strength of the tape. At the same time, the synergistic effect of nano-treated rubber and nano-level fly ash can improve the bonding performance of the tape. The addition of fly ash not only enhances the strength and hardness of the tape, but its waste utilization characteristics also help to reduce production costs. The combined use of natural animal and plant oils and mineral oils increases the lubricity and antioxidant properties of the tape, thereby reducing the friction coefficient of the tape during use, reducing the wear of the tape, and extending the life of the tape. The new combination of the above raw materials enables the finished tape to maintain stable performance while achieving environmental protection and economic purposes.
[0111] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A soft polyvinyl chloride electrical tape, characterized in that: The adhesive tape raw materials are composed of a base film raw material part and an adhesive layer raw material part, and the adhesive tape raw materials and their weight parts are: 45-52 parts of polyvinyl chloride; 15-20 parts of polylactic acid; 1-4 parts of polybutylene terephthalate-adipate; 45-60 parts of benzoate plasticizer; 14-18 parts of nano-treated rubber; 1.2-1.5 parts of calcium zinc stabilizer; 5-8 parts of color paste; 5-20 parts of nano-level fly ash; 4-7 parts of trioctyl trimellitate; 8-14 parts of thermoplastic polyurethane; 8-17 parts of tin-doped porous silica; 14-20 parts of natural animal and vegetable oils and mineral oils; 6-10 parts of molybdenum oxide; 9-14 parts of tripropane ester; 22-30 parts of ethanol; and 35-40 parts of water.
2. A soft polyvinyl chloride electrical tape according to claim 1, characterized in that: The nano-treatment process of the nano-treated rubber is as follows: natural rubber and nano-silicon dioxide are mixed in a weight ratio of 1:4, and the mixture is cut and evenly dispersed by a high-speed shearing stirrer to form a nano-treated rubber raw material.
3. The soft polyvinyl chloride electrical tape according to claim 1, characterized in that: The preparation process of the nano-scale fly ash is as follows: fly ash with a silicon dioxide content of 20% is selected as the basic material, and the fly ash is put into a jet mill for pulverization to make the particle size reach the raw material with an average diameter of 60-80nm.
4. The soft polyvinyl chloride electrical tape according to claim 1, characterized in that: The weight ratio of the natural animal and plant oils to the mineral oil is 6:
1.
5. A method for processing a soft polyvinyl chloride electrical tape, characterized in that: The raw materials of the soft polyvinyl chloride electrical tape according to claim 1 and the weight parts thereof are processed, comprising the following processing steps: Step 1: Raw material preparation: prepare all raw materials in the raw material formula by weight; Step 2, solvent selection: select ethanol and water as solvent; Step 3, base film preparation: polyvinyl chloride, polylactic acid and polybutylene terephthalate-adipate are added into a mixing kettle A, ethanol and water are added, and after setting conditions, mixing, heating and stirring are performed, and the base film is formed by extruding through an extruder; Step 4, adhesive layer part: add benzoate plasticizer, nano-treated rubber, calcium zinc stabilizer, color paste, nano-scale fly ash, trioctyl trimellitate, thermoplastic polyurethane, tin-doped porous silica, natural animal and vegetable oils and mineral oils, molybdenum oxide and tripropane ester into another mixing kettle B, add the remaining ethanol and water, set the conditions, mix, heat and stir to form an adhesive layer solution; Step 5: coating: coating the prepared adhesive layer solution on the base film; Step 6: Curing: The coated base film is placed in an oven for drying, and the finished electrical tape is produced; Step 7. Quality inspection: Test the appearance, thickness, width, bonding strength and electrical performance of the finished electrical tape.
6. The method for processing a soft polyvinyl chloride electrical tape according to claim 5, characterized in that: The setting conditions of step three are: setting the temperature of mixing kettle A to 78-85°C, setting the stirring speed of mixing kettle A to 100r / min, setting the temperature of extruder to 60-80°C, and setting the calendering speed of extruder to 2.5-3.5m / min.
7. The method for processing a soft polyvinyl chloride electrical tape according to claim 5, characterized in that: The setting conditions of step 4 are: setting the temperature of mixing kettle B to 60-65° C., and setting the stirring speed of mixing kettle B to 200 r / min.
8. The method for processing a soft polyvinyl chloride electrical tape according to claim 5, characterized in that: The weight ratio of ethanol to water in step three is 6:2, and the weight ratio of ethanol to water in step four is 5:
4.
9. The method for processing a soft polyvinyl chloride electrical tape according to claim 5, characterized in that: In the step five, a coating machine is used to coat the prepared adhesive layer solution on the base film, and the coating thickness is controlled between 0.12 mm and 0.14 mm.
10. The method for processing a soft polyvinyl chloride electrical tape according to claim 5, characterized in that: The curing temperature in step six is 100-105° C., and after curing, the mixture is cooled to room temperature under natural conditions.
Citation Information
Patent Citations
Process for processing adhesives for decorative sheets
CN103409097A
Preparation method of degradable PVC film and adhesive tape
CN116355327A
Degradable adhesive tape as well as preparation method and application thereof
CN118271987A
Adhesive tape
JP2023013841A